PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF PADA MATERI SEGIEMPAT DAN SEGITIGA UNTUK PESERTA DIDIK KELAS VII SMP - Maifina Alpionora (Jurnal Edukasi dan Penelitian Matematika, 2021)
This study aims to produce interactive learning multimedia on quadrilateral and triangular matter and to determine the quality of multimedia developed based on validity and practicality aspects. This type of research is a development research with a Plomp model consisting of a preliminary research stage and a prototyping phase. Research data were collected by observation, interviews, and questionnaires. The results of this study are: (1) Interactive learning multimedia has a very valid category based on the average result of the validator's assessment of 88.62%, (2) Interactive learning multimedia has a very practical category based on the average results obtained from the response questionnaire sheet. students of 90.74%. Based on these results, it can be concluded that the resulting interactive learning multimedia is valid and practical. Keywords  – interactive learning multimedia, quadrilateral and triangular, Plomp